Cross-validation and modifications of the perceived mattering questionnaire—Physical education in Chinese inservice physical education teachers - Zhang, Xin; Liu, Jingwen; Liu, Xiaolu; Shangguan, Rulan; Hamilton, Xiaofen D.; Guan, Jianmin; Bridges, Dwan (Frontiers in Psychology, 2022)
This study aimed to provide evidence of validity and reliability for the Perceived Mattering Questionnaire-Physical Education (PMQ-PE) developed by Richards et al. (2017) for the Chinese physical education (PE) teachers. The PMQ-PE consisted of two factors (i.e., PE matters and PE teacher matters) with four items in each, measuring four dimensions (attention, importance, dependence, and ego-extension). PMQ-PE in Chinese (PMQ-PEC) was validated among 1,278 elementary and secondary school PE teachers in China, of whom 59.0% were secondary PE teachers and 70.2% were males. Confirmatory factor analysis (CFA) with the entire sample found a poor model fit. Then exploratory factor analysis (EFA) using half of the sample indicated there was only one factor in PMQ-PEC. CFA of the other half of the sample suggested a one-factor model with the elimination of three unfitted items showed a better fitness to the data. Cronbach's alpha value was also acceptable. The final version of PMQ-PEC included five items with one factor that demonstrated acceptable validity and reliability and was deemed acceptable among Chinese PE teachers after the above modifications were made.